Macrophage phenotype in response to ECM bioscaffolds - Huleihel, Luai; Dziki, Jenna L.; Bartolacci, Joseph G.; Rausch, Theresa; Scarritt, Michelle E.; Cramer, Madeline C.; Vorobyov, Tatiana; LoPresti, Samuel T.; Swinehart, Ilea T.; White, Lisa J.; Brown, Bryan N.; Badylak, Stephen F (Elsevier, 2017)
Macrophage presence and phenotype are critical determinants of the healing response following injury. Downregulation of the pro-inflammatory macrophage phenotype has been associated with the therapeutic use of bioscaffolds composed of extracellular matrix (ECM), but phenotypic characterization of macrophages has typically been limited to small number of non-specific cell surface markers or expressed proteins. The present study determined the response of both primary murine bone marrow derived macrophages (BMDM) and a transformed human mononuclear cell line (THP-1 cells) to degradation products of two different, commonly used ECM bioscaffolds; urinary bladder matrix (UBM-ECM) and small intestinal submucosa (SIS-ECM). Quantified cell responses included gene expression, protein expression, commonly used cell surface markers, and functional assays. Results showed that the phenotype elicited by ECM exposure (MECM) is distinct from both the classically activated IFNγ + LPS phenotype and the alternatively activated IL-4 phenotype. Furthermore, the BMDM and THP-1 macrophages responded differently to identical stimuli, and UBM-ECM and SIS-ECM bioscaffolds induced similar, yet distinct phenotypic profiles. The results of this study not only characterized an MECM phenotype that has anti-inflammatory traits but also showed the risks and challenges of making conclusions about the role of macrophage mediated events without consideration of the source of macrophages and the limitations of individual cell markers.